The impact of human resources information systems on individual innovation capability in Tunisian companies: The moderating role of affective commitment - Nejib Ben Moussa; Rakia El Arbi (European Research on Management and Business Economics (ERMBE), 2020)
This research focuses on the study of the impact of the HRIS' use in human resources department (HR) on individual innovation capability. A research model was proposed and the related hypotheses were tested within human resources department of Tunisian companies with 42 respondents. Results estimated by Smart PLS software, showed that HRIS usage enhances individual innovation capability of Tunisian HR employees. Moreover, it has been found that employees' affective commitment moderates the relationship between HRIS usage and individual innovation capability. In fact, more the employees are engaged affectively to their organization more the HRIS impact is positive and noteworthy on individual innovation behavior of HR staff. The study allows clarifying some lines which are responsible of improving individual creativity.
Keywords: M15; M31; 650; Human resource information system; Individual innovation capability; Affective commitment; Creativity